Long-term respiratory outcomes of post-op congenital lung malformations - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; KIYAN, GÜRSU; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background Congenital lung malformations (CLM) are rare disorders and surgical intervention is the definitive treatment. Our aim is to evaluate the long-term lung function of patients with CLM after surgery compared to healthy children. Methods Sixteen children with CLM (M/F: 9/7) and 30 age-matched, healthy controls (M/F: 13/17) were included in the study. Demographic data were recorded and both groups were compared by spirometry and the nitrogen-based Lung Clearance Index (LCI). Results Mean +/- SD age of the patients was 12.0 +/- 5.4 years. The mean forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC, and forced expiratory flow between 25% and 75% of force expiration (FEF25-75) predicted was, 86.68 +/- 16.65, 88.00 +/- 14.58, 97.44 +/- 9.89, and 79.00 +/- 26.41, respectively in the patient group. Patients with CLM had significantly lower values in FEV1, FVC, FEF25-75 than healthy controls (P = 0.002, P 0.007, P 0.045). While the mean LCI2,5% value in patients' group was 8.33 +/- 1.52, it was 7.28 +/- 0.80 in healthy controls (P = 0.023). Strong inverse correlation between LCI and FEV1, FEV1/FVC was detected in the patient group (P = 0.023; r: -0.581, P 0.017; r: -0.606 respectively). Conclusion This study revealed that, in long-term follow-up, patients who had surgery because of CLM have impairment in the pulmonary function compared to healthy children and LCI may be more accurate in detecting airway diseases early than spirometry.
Keywords: congenital lung malformations; lung clearance index; pulmonary function test; spirometry; INERT-GAS WASHOUT; MULTIPLE-BREATH WASHOUT; PULMONARY-FUNCTION; CLEARANCE INDEX; CHILDREN; LOBECTOMY; DISEASE; STATEMENT; CHILDHOOD; RESECTION